Kontribusi Pasar Kalangan dan Faktor Penentu Ketahanan Pangan Rumah Tangga Petani Karet di Desa Tanjung Raya Kecamatan Rambang Muara Enim - Yunita, Yunita; Setiawan, M. (Seminar Nasional Lahan Suboptimal, 2023)
Yunita & Setiawan, M. (2023). Local market contribution and determining factors of food security of rubber farming households in Tanjung Raya Village, Rambang District Muara Enim. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 635-648).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The purposes of this search were to: (1) Analyzing the contribution of the circle market to the fulfillment of household food of rubber farmers in Tanjung Raya Village, Rambang District (2). Analyzing the condition of food security of rubber farmer households in Tanjung Raya Village, Rambang Subdistrict. (3) Analyzing the factors that influence the food security of rubber farmer households in Tanjung Raya Village, Rambang Subdistrict. This research was conducted in Tanjung Raya Village, Rambang Subdistrict, Muara Enim Regency. The determination of the location was carried out deliberately with the research method used, namely the survey method. Data collection was conducted in February 2023. The sampling method used was purposive sampling. The data used are primary data and secondary data. Primary data was obtained through direct field interviews with sample farmer, while secondary data obtained from the office or related institutions. The results showed that the circle market contributed to meeting the food needs of rubber farmer households with a percentage of 54 percent. The share of food expenditure of rubber farmer households is 46.3 percent, indicating that farmer households are food secure. Factors that significantly affect the food security of rubber farmer households were income, number of family members, household expenditure, and rice expenditure.